On people’s perceptions of climate change and its impacts in a hotspot of global warming - Parbati Phuyal; Isabelle Marie Kramer; Indira Kadel; Edwin Wouters; Axel Magdeburg; David A. Groneberg; Ulrich Kuch; Bodo Ahrens; Mandira Lamichhane Dhimal; Meghnath Dhimal; Ruth Muller (PLoS ONE, 2025)
The Hindu Kush Himalayan region is a global hotspot for climate change and highly vulnerable to its direct and indirect impacts. Understanding people’s perception of climate change is crucial for effective adaptation strategies. We conducted a study by using quantitative (Household survey, n = 660) and qualitative data collection tools (Focus group discussion, n = 12; In-depth interviews, n = 27) in central Nepal encompassing three altitudinal regions: Lowland (<1000 m amsl; Terai region), Midland (1000–1500 m amsl; hilly region) and Highland (1500–2100 m amsl; mountainous region). We analyzed 37 years (1981–2017) of climatic data from respective districts (Lowland: Chitwan, Dhading; Midland: Kathmandu, Lalitpur; Highland: Nuwakot, Rasuwa). People’s perception was compared with climate extreme indices measured along these regions and evaluated if they accurately recognized the impacts on the environment and human health. Our findings show significant climate changes, including rising summer temperature, region-specific winter temperatures and extended monsoon seasons in Nepal. Participants in our study accurately perceived these trends but misperceived heavy precipitation patterns. Reported impacts are rise in crop diseases, human diseases, vector expansion and climate induced disasters like floods, landslides, and water resource depletion, with perception accuracy varying by region. These insights highlight the importance of understanding regional and cross-regional perceptions in relation to climate data in order to develop tailored climate adaptation strategies. Policymakers can use this information to establish region-specific educational and communication initiatives, addressing communities’ distinctive vulnerabilities and needs across diverse landscapes. Such approaches can enhance equitable and effective climate resilience in subtropical to alpine regions.